Probing the electronic environment of binary and ternary ionic liquid mixtures by x-ray photoelectron spectroscopy - Men, Shuang; Licence, Peter (Elsevier, 2017)
X-ray photoelectron spectroscopy is used to probe the electronic environment of cations and anions for three binary and one ternary chlorostannate ionic liquid mixtures. The impact of the weighting of Cl on the electronic environment of the cation-based nitrogen atom is revealed in detail. With the increasing of the concentration of Cl , the N 1s binding energy is decreased. The electronic environment of the anion- based component is also compared based upon Sn 3d5/2 and Cl 2p3/2 binding energies. It is found that with the increasing of the weighting of Cl , binding energies of Sn 3d5/2 and Cl 2p3/2 both decrease.